Author Correction: Sensory innervation in porous endplates by Netrin-1 from osteoclasts mediates PGE2-induced spinal hypersensitivity in mice - Shuangfei Ni (Nature Portfolio, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.